2015
DOI: 10.3201/eid2111.150608
|View full text |Cite
|
Sign up to set email alerts
|

Encephalitis-Associated Human Metapneumovirus Pneumonia in Adult, Australia

Abstract: Human metapneumovirus pneumonia, most commonly found in children, was diagnosed in an adult with encephalitis. This case suggests that testing for human metapneumovirus RNA in nasopharyngeal aspirate and cerebrospinal fluid samples should be considered in adults with encephalitis who have a preceding respiratory infection,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…As in the study by Fok et al ( 4 ), our case supports consideration of HMPV as a causative agent of acute encephalitis after respiratory tract infection in adults. We could not demonstrate direct or indirect evidence of HMPV CSF invasion as the cause for HMPV-associated encephalitis in an adult, in contrast to a case in a child in which detection of HMPV in CSF suggested a causative role in acute encephalitis ( 1 ).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…As in the study by Fok et al ( 4 ), our case supports consideration of HMPV as a causative agent of acute encephalitis after respiratory tract infection in adults. We could not demonstrate direct or indirect evidence of HMPV CSF invasion as the cause for HMPV-associated encephalitis in an adult, in contrast to a case in a child in which detection of HMPV in CSF suggested a causative role in acute encephalitis ( 1 ).…”
supporting
confidence: 90%
“…Recently, Fok et al ( 4 ) described an encephalitis case in an adult but were unable to test cerebrospinal fluid (CSF) for HMPV. Following authors’ recommendations, we performed diagnostic testing on the CSF of an adult with HMPV-associated encephalitis.…”
mentioning
confidence: 99%
“…During the last two decades, sporadic cases of febrile seizures, encephalitis and encephalopathies (associated with epileptic symptoms) have been described. Viral material was detected within the CNS in some clinical cases of encephalitis/encephalopathy [130][131][132][133][134] but, at present, no experimental data from any animal model exist that would help to understand the underlying mechanism associated with hMPV neuroinvasion and potential neurovirulence.…”
Section: Respiratory Viruses With Neuroinvasive and Neurotropic Propementioning
confidence: 99%
“…In addition to respiratory diseases, hMPV has been associated with neurological complications in a handful of cases (acute encephalopathy, encephalitis, and seizures) reported in the literature. [7][8][9][10][11][12][13][14][15] The "California Encephalitis Project, 1998-2000" concluded that the etiological diagnosis of encephalitis remains inconclusive in more than two thirds of cases despite extensive testing. 16 The results of the California Encephalitis Project were reported before hMPV was described as a virus and thus it may be one cause of some of the unknowns.…”
Section: Discussionmentioning
confidence: 99%